PERBANDINGAN PROJECT BASED LEARNING DAN GUIDED INQUIRY PADA PENGEMBANGAN PEMAHAMAN KONSEP PESERTA DIDIK SMA - La Ode Kaharudin; Veni Rosnawati (Academy of Education Journal, 2020)
Comparison of Project Based Learning and Guided Inquiry in the Development of Understanding of High School Student Concepts. This study aims to compare the understanding of concepts in the Excretion System material between students taught using Project Based Learning (PjBL) and Guided Inquiry (GI). This research is in the form of a quasi experiment with a pretest-posttest non-equivalent control group design. The population of this research is the XI grade students of SMA Negeri 1 Kendari, 2018/2019 Academic Year. The sample of this study was students of Class XI MIPA 1 as an experimental group taught by the PjBL model and students of Class XI MIPA 2, taught by the GI model. Data were analyzed descriptively and inferentially using the SPSS program. The conclusions of this study are (1) There is a significant difference in the understanding of concepts in the excretion system material between students taught with project based learning models and students taught with guided inquiry models as evidenced by differences in the average value of students' posttest and G-gain value in each indicator of concept understanding, (2) Students of the project based learning model class gain significantly higher concept understanding than the group of students in the guided inquiry model class.